Space and Control in Soccer - Martens, Florian; Dick, Uwe; Brefeld, Ulf (Frontiers in Sports and Active Living, 2021)
In many team sports, the ability to control and generate space in dangerous areas on the pitch is crucial for a team's success. This holds in particular for soccer. In this paper, we revisit ideas from Fernandez & Bornn (2018) who introduce interesting space-related quantities including pitch control and pitch value. We identify player influence on the pitch with player movements and turn their concepts into data-driven quantities that give rise to a variety of different applications. Furthermore, we devise a novel space generation measure to visualize team and player strategies. We provide empirical evidence for the usefulness of our contribution and showcase our approach in the context of game analyses.